Insights into the Structure-Capacity of Food Antioxidant Compounds Assessed Using Coulometry - Francesco Siano; Anna Sofia Sammarco; Olga Fierro; Domenico Castaldo; Tonino Caruso; Gianluca Picariello; Ermanno Vasca (MDPI AG, 2023)
CDAC (coulometrically determined antioxidant capacity) involves the determination of the antioxidant capacity of individual compounds or their mixtures using constant-current coulometry, with electrogenerated Br2 as the titrant, and biamperometric detection of the endpoint via Br2 excess. CDAC is an accurate, sensitive, rapid, and cheap measurement of the mol electrons (mol e−) transferred in a redox process. In this study, the CDAC of 48 individual antioxidants commonly found in foods has been determined. The molar ratio CDAC (CDACχ, mol e− mol−1) of representative antioxidants is ranked as follows: tannic acid > malvidin-3-O-glucoside ≃ curcumin > quercetin > catechin ≃ ellagic acid > gallic acid > tyrosol > BHT ≃ hydroxytyrosol > chlorogenic acid ≃ ascorbic acid ≃ Trolox®. In many cases, the CDACχ ranking of the flavonoids did not comply with the structural motifs that promote electron or hydrogen atom transfers, known as the Bors criteria. As an accurate esteem of the stoichiometric coefficients for reactions of antioxidants with Br2, the CDACχ provides insights into the structure-activity relationships underlying (electro)chemical reactions. The electrochemical ratio (ER), defined as the antioxidant capacity of individual compounds relative to ascorbic acid, represents a dimensionless nutritional index that can be used to estimate the antioxidant power of any foods on an additive basis.